The garden, the curtain and the cross - Laferton, Carl ([UK] : The Good Book Company, 2016)
"Read the amazing story of the whole Bible, why Jesus died and rose again, and how you can be part of the story."--Page [4] of cover.
Keywords: Jesus Christ -- Crucifixion -- Juvenile literature; Redemption -- Christianity -- Juvenile literature; Salvation -- Biblical teaching -- Juvenile literature; Jesus Christ -- Crucifixion; Redemption -- Christianity; Salvation -- Christianity